'Man sorting books': historical research in an archive of university photographs. Issue 1 (2nd January 2019) - Kelly, Frances
ABSTRACT: The impetus for this article was an encounter with thousands of photographs in an online archive of a public university in New Zealand, taken over the twentieth century. The size of the archive and the paucity of information about many images draws attention to challenges of commencing work in a large institutional visual archive. The first part of the article outlines initial forays into the archive and attempts to 'sort' the 22, 000 plus images it contains into some form of order, utilising the categories of people, things, spaces, activities. The second part considers the history of the library as integral to an idea of the university and its role in the storing, organisation and dissemination of knowledge. It analyses archival images of the library to reflect on its place in the university, together with the limits and opportunities afforded by visual archives in histories of higher education.